Dynamics of wall heated packed bed reactors - Subbarao, D. (Trans Tech Publications Ltd, 2014)
The multi-tubular packed bed reactors in shell tube heat exchanger configuration are widely used for carrying out exo-/endo- thermic reactions. To design control strategies for stable and safe operation of such reactors, information on dynamic response of such units are needed. Dynamic response of a pilot scale multi-tubular packed bed reactors in shell tube heat exchanger configuration performing dehydrogenation of isopropyl alcohol are presented. Â© 2014 Trans Tech Publications, Switzerland.